(untitled) (CIPEEX, 2022)
BREAST CANCER IS THE LEADING CAUSE OF CANCER DEATH IN WOMEN AROUND THE WORLD. TRIPLE-NEGATIVE BREAST CANCER (CMTN) IS A HETEROGENEOUS AND MORE AGGRESSIVE SUBSET OF NEOPLASMS THAT IS DEFINED BY THE ABSENCE OF TARGET RECEPTORS, THUS BEING RESISTANT TO TARGET THERAPIES AND CHEMOTHERAPY. THE NEED FOR MORE EFFECTIVE DRUGS WITH LESS ADVERSE REACTIONS HAS GENERATED EFFORTS FOR THE DEVELOPMENT OF ALTERNATIVE CHEMOTHERAPEUTIC AGENTS, MAINLY FROM PLANT COMPOUNDS AND OTHER NATURAL SOURCES SUCH AS GALLIC ACID (GA). STUDIES SHOW THAT AG HAS ANTIOXIDANT, ANTITUMOR AND ANTIANGIOGENIC ACTIVITY IN VITRO, CAPABLE OF PROMOTING DEATH BY APOPTOSIS AND INHIBITING CELL PROLIFERATION. THIS WORK AIMS TO VERIFY THE ANTINEOPLASTIC POTENTIAL OF AG IN BREAST CANCER CELL LINE MDA-MB-231. FOR THIS, THE CELLS WILL BE CULTURED IN DULBECCO MODIFIED EAGLE’S MEDIUM (DMEM), WITH HIGH GLUCOSE CONCENTRATION PLUS 10% FETAL BOVINE SERUM, PENICILLIN AND STREPTOMYCIN, AMPHOTERICIN B AND L GLUTAMINE. THE AG TREATMENTS WILL BE DONE WITH THE DOSES OF 15, 30, AND 60 Î¼MOL / L NEGATIVE CONTROL GROUP FOR THREE DIFFERENT PERIODS FOR EACH CONCENTRATION, FOR 24 H (G24), 48 H (G48) AND 72 H (G48) G72). CELL VIABILITY AND CYTOTOXICITY WILL BE ANALYZED BY THE TRIPAN BLUE EXCLUSION METHOD AND TETRAZOLIUM REDUCTION METHOD (MTT). IT IS EXPECTED THAT AFTER THE USE OF GA TUMOR CELLS HAVE LOW CELL VIABILITY, EXPRESSIVE CYTOTOXIC EFFECT, AND THAT CONCENTRATION AND TIME OF EXPOSURE INFLUENCE CYTOTOXICITY AND CELL VIABILITY.